"After you, sir!": Substitution in Kant and Levinas. Issue 48 (3rd April 2017) - Smith, Daniel
ABSTRACT: This paper compares the later Levinas' notion of "substitution" with Kant's account of substitution in Religion within the Boundaries of Mere Reason . Kant's account is modelled on the Christian doctrine of the vicarious substitution of Christ, and some recent commentators on Levinas have argued that Levinas' account is also similar to this Christian doctrine. By bringing out what I see as major differences between the two accounts, I show that Levinas' notion of substitution should not be understood in this way.